Stator Dynamics Depending on Sodium Concentration in Sodium-Driven Bacterial Flagellar Motors - Lin, Tsai-Shun; Kojima, Seiji; Fukuoka, Hajime; Ishijima, Akihiko; Homma, Michio; Lo, Chien-Jung (Frontiers in Microbiology, 2021)
Bacterial flagellar motor (BFM) is a large membrane-spanning molecular rotary machine for swimming motility. Torque is generated by the interaction between the rotor and multiple stator units powered by ion motive force (IMF). The number of bound stator units is dynamically changed in response to the external load and the IMF. However, the detailed dynamics of stator units exchange process remain unclear. Here we directly measured the speed changes of sodium-driven chimaeric BFMs under fast perfusion of different sodium concentration conditions using computer-controlled high-throughput microfluidic devices. We found the sodium-driven chimaeric BFMs maintained constant speed over a wide range of sodium concentrations by adjusting stator units in compensation to the sodium-motive force (SMF) changes. The BFM has the maximum number of stator units and is most stable at 5 mM sodium concentration rather than higher sodium concentration. Upon rapid exchange from high to low sodium concentration, the stator number shows a drop and then resurrection that is different from predictions of simple absorption model. This may imply the existence of a metastable hidden state of the stator unit during the sudden loss of sodium ions.